Transposon-specified site-specific recombination. - Kitts, P (1982)
Cointegrate DNA molecules containing two copies of a transposable element appear to be intermediates in the transposition process. These structures are resolved by site-specific recombination to yield the normal end products of transposition. The transposable element gamma delta (Tn1000) synthesizes a product interchangeable with the Tn1/3tnpR protein in promoting Tn1/3 site-specific recombination. These data support the hypothesis that cointegrates containing directly repeated copies of Tn1/3 are obligatory intermediates in interreplicon transposition of Tn1/3. In addition, we show here that the reaction is independent of the element-encoded tnpA gene product. Tn501, which specifies mercury resistance, also produces cointegrates as intermediates in interreplicon transposition. The appearance of Tn501-specified recombination activity that can act on these cointegrates requires growth of cells in the presence of Hg2+.